2021
DOI: 10.3390/md19080465
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of A549 Lung Cancer Cell Migration and Invasion by Ent-Caprolactin C via the Suppression of Transforming Growth Factor-β-Induced Epithelial—Mesenchymal Transition

Abstract: The epithelial–mesenchymal transition (EMT) of cancer cells is a crucial process in cancer cell metastasis. An Aquimarina sp. MC085 extract was found to inhibit A549 human lung cancer cell invasion, and caprolactin C (1), a new natural product, α-amino-ε-caprolactam linked to 3-methyl butanoic acid, was purified through bioactivity-guided isolation of the extract. Furthermore, its enantiomeric compound, ent-caprolactin C (2), was synthesized. Both 1 and 2 inhibited the invasion and γ-irradiation-induced migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Both caprolactin C and its synthetic enantiomer inhibited the invasion and migration of A549 lung cancer cells, but only the unnatural compound was found to suppress transforming growth factor-β (TGF-β) induced epithelial–mesenchymal transition (EMT), thus this molecule may hold promise as a potential lead candidate for development of new antimetastatic agents. 5 The Bacillus genus yielded a number of new metabolites in 2021 including a diketopiperazine 7 , 6 an antimicrobial oxatetracyclo ketone 8 , 7 bacillibactins E 9 and F 10 , which are the first bacterial siderophores that contain nicotinic and benzoic acid moieties, 8 and the anti-mycoplasma active cyclic lipodepsipeptides, bacilotetrins C–E 11–13 . This latter study also involved the structure revision of the previously reported bacilotetrin A 14 and bacilotetrin B 15 , 16 that was deemed to be a mixture of two isomers.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…Both caprolactin C and its synthetic enantiomer inhibited the invasion and migration of A549 lung cancer cells, but only the unnatural compound was found to suppress transforming growth factor-β (TGF-β) induced epithelial–mesenchymal transition (EMT), thus this molecule may hold promise as a potential lead candidate for development of new antimetastatic agents. 5 The Bacillus genus yielded a number of new metabolites in 2021 including a diketopiperazine 7 , 6 an antimicrobial oxatetracyclo ketone 8 , 7 bacillibactins E 9 and F 10 , which are the first bacterial siderophores that contain nicotinic and benzoic acid moieties, 8 and the anti-mycoplasma active cyclic lipodepsipeptides, bacilotetrins C–E 11–13 . This latter study also involved the structure revision of the previously reported bacilotetrin A 14 and bacilotetrin B 15 , 16 that was deemed to be a mixture of two isomers.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The first total syntheses of 22 marine bacterial compounds was reported in the literature during 2021, caprolactin C 6 , 5 akazaoxime 4 and A-76356 45 , 16 MA026 67 , 25 xiamycins D and E, 69 bacicyclin, 70 (+)-pseudonocardide A and (+)-pseudonocardide C, 71 nocardiotide A, 72 three 2-( p -hydroxybenzyl)-prodigiosin-based MNPs, along with isoheptylprodigiosin, and tambjamine MYP1, 73 (+)-spiroindimicin A, 74 nesteretal A, 75 (+)-03219A, 76 enterocin, 77 nahuoic acid A, 78 piscibactin, 79 and aldgamycin N. 80…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The migration assay was conducted using a Cell Culture Insert with a pore size of 8 μm (BD Biosciences, Bedford, MA, U.S.A.) as previously described (32). Matrigel LDEV-Free Reduced Growth Factor Basement Membrane Matrix (Thermo Fisher Scientific, San Diego, CA, U.S.A.) was used to evaluate cell invasion potential.…”
Section: Cell Migration Invasion and Wound Healing Measurementsmentioning
confidence: 99%
“…In a dose-dependent manner, TGF-β or, alternatively, ginsenosides Rk1 and Rg5 treatment in NSCLC A549 cells, regulate EMT by suppressing the Smad and NF-kB/ERK pathways (non-Smad pathway) [ 42 ]. In A549 cells, ginsenoside CK prevents TGF-β-induced EMT and metastasis [ 43 ]; furthermore, in TGF-β-treated A549 cells, a novel compound called ent -caprolactin C inhibited the phosphorylation of Smad2/3 and suppressed the EMT cell marker proteins, so that TGF-β-induced EMT was inhibited, constituting a potential antimetastatic agent [ 44 ]. In addition, TGF-β induced the reprogramming of the amino acid metabolism, necessary to EMT in NSCLC, which depends on prolyl 4-hydroxylase α3 (P4HA3), an enzyme implicated in cancer metabolism; if downregulated, this promotes TGF-β-dependent changes in amino acids inhibition and EMT, and consequently tumor metastasis occurred [ 45 ].…”
Section: Tgf-β Molecular Mechanism In Lung Cancermentioning
confidence: 99%